The Effect of Using the Obstetrics and Gynecology Logbook on the Clinical Skills of Interns and Trainees - Zohreh Khazaee; Tahereh Khazaee; Maleknaz Ghannadkafi; Mohammad Zaher Ibrahimi (Kerman University of Medical Sciences, 2013)
Background & Objective: Preidentification of practical educational objectives and provision of equal learning opportunities corresponding to the objectives for students are among the needs of the educational system that should be fulfilled using the clinical handbook (Logbook) The current research tried to assess the effect of using this handbook on the learning of the students of the department of obstetrics and gynecology Methods: This quasiexperimental study was carried out on 117 medical students composed of trainees and interns in the academic year 20102011 The students were randomly divided into an experimental group and a control group The experimental group participants were trained with the help of the logbook while the control groups training followed the normal established method The skills of the two groups were evaluated at the end of the term through direct observation based on a checklist Results: The average of the total scores of the trainees and the interns of the experimental group was significantly higher than that of the control group (P < 005) However with regard to a number of skills there was no difference between the scores of the trainees of the two groups Conclusion: The Logbook is efficient but not sufficient for teaching clinical skills and therefore there should be an appropriate ground for a more efficient usage of the book